Makna Simbolik dalam Upacara Adat Sedekah Bumi Desa Pelem Kecamatan Gabus Kabupaten Grobogan - Henny Puspita Sari; Yanti Haryanti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
This research explores the symbolic meanings within the traditional ceremony of "sedekah bumi" in Pelem Village, Gabus Subdistrict, Grobogan Regency. Employing a phenomenological approach, data was gathered through interviews and documentation, with focused data analysis involving reduction, presentation, and conclusion drawing. The findings indicate that the traditional ceremony serves as an expression of gratitude and a harmonious connection with nature. The community engages in collaborative activities, rituals, and prayers as a form of reverence to God and the surrounding environment. Despite perceptual differences between the younger generation and elders regarding the relevance of the tradition, the traditional ceremony persists to preserve cultural identity and heritage values. The impact of differing societal perceptions creates social dynamics reflecting generational conflicts and cultural changes. This research provides profound insights into the importance of communicating cultural values to maintain a balance between tradition and positive development in a multicultural society.